Microstrip dual mode multi-bandpass filters based on tree fractal slotted resonator for wireless communication - Manju Bhaskar; Thomaskutty Mathew (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2019)
Dual mode microstrip multi-bandpass filter is proposed with tree fractal slot on a square patch resonator. The tree fractal slotted resonators are generated from conventional square patch using an iterative tree fractal generator method. A single square patch is used for realizing both dual and tri-bandpass filters exploiting the dominant, higher order and its corresponding degenerate resonant modes by the tree fractal iteration on the diagonal unequal slots on the square patch.The resonant peaks, transmission zeros and bandwidth of the pass bands can be tuned by varying the length and width of the fractal slot. By optimizing various parameters dual mode dual and tri-band pass filters are simulated, fabricated and measured. The proposed filter finds application in wireless communication devices and falls in the bands of GSM, WLAN, Bluetooth, Zigbee, WiMax and WiFi.